Carbohydrate Intake Of Medical Students And Its Relation To Waist Circumference And Blood Pressure - Irinne Karina Putri; Ardesy Melizah Kurniati; Swanny Swanny; Liniyanti D. Oswari; Veny Larasaty; Syarinta Adenina (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Introduction. Metabolic syndrome is the constellation of metabolic abnormalities that are associated with an increased risk of cardiovascular disease and diabetes melitus. The prevalence of metabolic syndrome in younger people is increasing along with the increased prevalence of obesity. Waist circumference and blood pressure measurement are simple examinations for early detection of metabolic syndrome. Excessive consumption of carbohydrates is one of the factors that cause health problems. But the data of these measurements and food records of medical students in Universitas Sriwijaya were not documented yet. Methods. This study was an observational analytic cross-sectional study with proportionate stratified random sampling. This study used primary data from forms, questionnaires, food records, and physical examinations collected from 275 medical students. The data were analyzed with an independent t-Test for normally distributed data or with Mann Whitney for not normally distributed data. Results. There was a significant relationship between carbohydrate intake and waist circumference (p-value = 0,048) but no relationship between carbohydrate intake and blood pressure (p-value for systolic blood pressure = 0,720 and diastolic blood pressure = 0,847). Conclusion. These findings show an association between carbohydrate intake and waist circumference, but no association between carbohydrate intake and blood pressure (systolic and diastolic blood pressure).